Full-field strain measurements at the micro-scale in fiber-reinforced composites using digital image correlation. (15th April 2016) - Mehdikhani, Mahoor; Aravand, Mohammadali; Sabuncuoglu, Baris; Callens, Michaël G.; Lomov, Stepan V.; Gorbatikh, Larissa
Abstract: Few studies have been conducted to monitor inter-fiber deformations in fiber-reinforced composites. In the present work, we demonstrate full-field strain measurements in the composites at the micro-scale, using digital image correlation (DIC). The study is performed on a unidirectional glass fiber reinforced composite loaded in transverse three-point bending inside an environmental scanning electron microscope. A nano-scale random speckle pattern of high quality is created. Validity of the measured fields is assessed against results of a finite element (FE) model with boundary conditions retrieved from the experiment. A good agreement is found between the DIC-measured and FE-predicted results. The precise recognition of very small-scale strain concentrations requires enhancement of the correlation process and removal of microscopy imperfections. The investigated methodology shows promise for real-time deformation measurements in composites at the micro-scale.